La condition enseignante en Guinée : des stratégies de survie dans le champ scolaire et universitaire guinéen - Ester Botta Somparé; Abdoulaye Wotem Somparé (Cahiers de la Recherche sur l'Education et les Savoirs)
This article demonstrates how Guinean teachers, facing difficult working and living conditions, develop strategies in order to improve their situation. We consider teachers as social actors endowed with agency, who do not rely only on the State, but rather on other actors of the educational field, such as pupils, parents, or founders of private schools. An analysis of teacher’s activities taking place beside their official mission (even though they often target their own pupils and take place inside the school buildings) shows how strategies vary according to the sociological profiles and geographic contexts, urban or rural.